Hindavi Nursery - Jambe nikita Motiram,; Bargal Sanika Santosh,; Jadhav Rahul Gorakh,; Ajabe Santosh Vilas,; Prof. Sayyed J.I, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In today’s fast-paced digital landscape, accessing desired products with minimal effort has become a standard expectation. However, when it comes to gardening and plant shopping, many individuals lack adequate knowledge or resources. This project introduces a user-centric web application designed to bridge the gap between plant sellers and buyers through a seamless e-commerce experience tailored specifically for the gardening sector. The platform empowers customers to explore plant varieties, compare prices, view detailed descriptions, and complete secure online transactions all from the comfort of their homes. It also supports both retail and wholesale purchasing to cater to domestic gardeners as well as commercial plantations. Beyond transactional features, the application offers educational content on plant care, technical support, and expert gardening advice to ensure a rewarding experience. Whether a user seeks a rare ornamental plant or bulk seeds for agriculture, this unified portal simplifies the process by eliminating traditional market barriers. By prioritizing customer convenience, satisfaction, and support, the platform transforms plant shopping into a smarter and more accessible endeavor for everyone.
Keywords: Plant E-Commerce; Online Nursery; Gardening Web App; Retail & Wholesale Plants; Customer Support; Online Plant Shopping; Green Technology; Smart Agriculture Platform